Evolutionary distribution and mode transition in medium frequency from 50 kHz to 5 MHz of argon atmospheric pressure dielectric barrier discharge plasma - Zhao, Zhibo; Yu, Yilin; Nie, Qiuyue; Zhang, Zhonglin (Frontiers in Physics, 2024)
Dielectric barrier discharges (DBDs) provide a promising technology of generating non-equilibrium cold plasmas in atmospheric pressure. For both application-focused and fundamental research, it is important to explore the discharge mode transition and electron heating mechanism to enable effective independent tuning of key plasma parameters in a DBD system. In this work, we report numerical studies of the effects of single-frequency excitation on atmospheric argon DBDs, which are carried out in the medium driving frequency (MF) range from 50 kHz to 5MHz by using a one-dimensional hydrodynamics coupling model. The spatio-temporal evolution of particle density associated with discharge mode transition and electron dynamics behaviour has been investigated. By tuning the different components of a single frequency, we observe the electron heating behaviors of the individual modes and the mode transitions from the Townsend discharge to the glow discharge in the low frequency to the Ω mode and the hybrid mode in the medium frequency to the α mode and the γ mode in the radio frequency. The physical analysis is understood based on these fundamental insights into the plasma physics.